Cardiac mechanics as predictors of left ventricular reverse remodelling in patients with dilated non-ischemic cardiomyopathy. (14th October 2021) - Ferrandez, M; Islas, F; Travieso, A; Diz-Diaz, J; Restrepo, A; Goirigolzarri, J; Luaces, M; De Agustin, J A; Bustos, A; Olmos, C
Abstract: Background and purpose: The appearance of left ventricular reverse remodelling (LVRR) is associated with a better prognosis in patients with dilated non-ischemic cardiomyopathy (DCM). Our aim was to identify cardiac imaging parameters, including speckle tracking by transthoracic echocardiography (TTE) and feature tracking by CMR, associated with LVRR in a prospective cohort of patients with DCM. Methods: From 2014 to 2021, 182 patients with DCM and left ventricle ejection fraction (LVEF) <40% were prospectively evaluated in our hospital. LVRR was defined as an increase in LVEF ≥10 points or absolute LVEF ≥50%, associated with a reduction in left ventricular end- diastolic diameter ≥10%. Patients underwent multimodality imaging evaluation including CMR with a 1.5 Tesla scanner, and TTE. Cardiac mechanics, including global longitudinal strain (GLS), strain rate (SR) and mechanical dispersion (MD) were measured. Results: Median age of our cohort was 62.3 (14.4) years, and 67.7% were male. Most patients (>90%) were treated with beta-blockers or RASS blockers, and 67% with mineralocorticoid receptor antagonists. 30% had cardiac resynchronization therapy (CRT) and 37% had ICD as primary prevention. Mean LVEF was 31.3%. During a mean follow-up period of 35.9 (35.4) months, 38.3% of patients had LVRR. Age and gender distribution were similar in both groups. Regarding cardiovascular risk factors and pharmacological treatment, no differences were found between patients with and without LVRR. Baseline CRT therapy was not associated with LVRR (22.6% vs 34.7%; p=0.249). However, there was a trend towards higher LVRR in those who received CRT during follow-up 18.8% vs 0%; p=0.069). Patients who experienced LVRR had lower basal LVEF (23.4% vs 29%; p<0.008), as well as poorer RV function, including lower RVEF (40.5% vs 51%; p=0.006) and lower TAPSE (16 mm vs 19 mm; p=0.021). Regarding cardiac mechanics, those patients with lower GLS (−9% vs −12%; p=0.001), and higher MD (73 mm vs 55 mm; p=0, 050) had LVRR more frequently during follow-up. The presence of a left bundle branch block (LBBB) contraction pattern by strain was associated with higher rate of LVRR (83.3% vs 30.4%; p=0.011). The burden of fibrosis measured by LGE with CMR was not associated with LVRR (14% vs 12%; p=NS). Patients with LVRR had a lower cardiovascular mortality (3.3 vs 14.3%; p=0.117), lower mortality due to heart failure (0% vs 12.2%; p=0.046), less heart failure hospitalizations (20% vs 46.9%; p=0.016), and a lower incidence of ventricular tachyarrhythmias (3.3% vs 18.4%; p=0.051). Conclusions: LVRR in patients with DCM receiving optimized medical therapy is associated with a better prognosis. Imaging parameters, including a lower basal LVEF, RVEF, GLS and higher MD, as well as LBBB echo pattern, were associated with a higher frequency of LVRR, and might help to identify patients who could benefit from CRT/and may be helpful to stratify patients's risk. Funding Acknowledgement: Type of funding sources: None.